ANALISIS FONOLOGIS BAHASA JAWA DI DESA TRIDADI KABUPATEN OKU TIMUR : DIALEKTOLOGI GEOGRAFI - Santika, Nova; Wardiah, Dessy; Hetilaniar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the phonological analysis of the Javanese language used by the people of Tridadi Village, East Ogan Komering Ulu Regency, using a geographical dialectology approach. The Javanese language that developed in the area is the result of the distribution of speakers from Java Island who experienced adaptation due to the influence of the geographical environment and contact with other regional languages ​​​​in the surrounding area. This study aims to describe phonological variations that include vowel phonemes, consonant phonemes, and phonetic correspondences in the speech of native speakers. The method used in this study is a qualitative method with data collection techniques in the form of observation, interviews, and recordings of three informants who are native Javanese speakers in Tridadi Village. The data obtained were then transcribed phonetically and analyzed using the distribution and matching methods. The results of the study indicate that there are 9 variations of vowel phonemes, namely /a, i, u, e, o, ɛ, ɔ, ə, ʊ/ and 19 variations of consonant phonemes, namely /b, c, d, g, h, j, k, l, m, n, ŋ, ɳ, p, r, s, t, w, y, ʔ/. These variations are influenced by geographical and social factors, as well as the existence of language contact with other regional languages ​​around the research area. In addition, sound correspondence patterns were also found that indicate certain phoneme changes in the context of speech. These phonological variations are characteristic of the Javanese dialect in Tridadi Village which distinguishes it from Javanese dialects in other areas. Thus, this study contributes to the development of phonological and dialectological studies, especially in describing Javanese language variations in the South Sumatra region.